2002
DOI: 10.1111/1467-6478.00227
|View full text |Cite
|
Sign up to set email alerts
|

Children at Risk: Legal and Societal Perceptions of the Potential Threat that the Possession of Child Pornography Poses to Society

Abstract: This article examines legal and social discourses surrounding the phenomenon of child pornography, considering the legal responses to child pornography (particularly when an individual is found to be in possession of such material), and the way in which such material, the child, and the possessor of child pornography are socially constructed.The article raises the question of whether there has been a moral panic regarding child pornography and the possession of such material, but also considers whether there a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 1 publication
1
14
0
Order By: Relevance
“…In child pornography such perception may be related to the age of the participants portrayed with relatively young children being the ones more likely to be perceived as relatively powerless. A similar point has been made by Suzanne Ost (2002):…”
Section: Parallels Between Adult and Child Pornographysupporting
confidence: 73%
“…In child pornography such perception may be related to the age of the participants portrayed with relatively young children being the ones more likely to be perceived as relatively powerless. A similar point has been made by Suzanne Ost (2002):…”
Section: Parallels Between Adult and Child Pornographysupporting
confidence: 73%
“…With regards to CSEM, authors such as Kuhnen (2007) and Ost (2002) consequently offending behavior (Calder, 2004;Quayle & Taylor, 2001). Also, in the development sample of the IBAQ (O" Brien & Webster, 2007), it was found that the more behavioral items an individual endorsed (i.e., those related to different online behaviors, such as which online facilities were visited by the offender or which methods were used to obtain CSEM from the Internet), the higher the attitudinal score obtained (i.e., those concerning the reinforcing nature of the Internet, or a portrayal of children as sexual objects).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…As noted at the outset, the meaning of grooming in a legal context is uncertain which does seem to reflect something of the phenomenon itself. Personal grooming, however, involves a series of what are, in terms of the literature, fairly wellestablished stages for manipulating children and normalizing deviant sexual relationships (Budin and Johnson, 1989;Conte et al, 1989;Conte, 1990, 1995;Elliott et al, 1995;Gallagher, 2000;Ost, 2002). First, grooming the child can typically include befriending a potential victim by getting to know their interests and being helpful and confiding in order to gain their confidence and trust.…”
Section: A Moral and Social Constructmentioning
confidence: 99%